PENERAPAN MODEL IMPROVING LEARNING DENGAN TEKNIK INKUIRI PADA POKOK BAHASAN TEOREMA PYTHAGORAS - Sanusi Sanusi (Faktor Jurnal Ilmiah Kependidikan, 2016)
Abstract: This research is motivated by the difficulties of the author as a mathematic teacher in improving the learning outcomes of mathematic. The subjects of this research were 44 students in grade VIII.2 SMPN 10 Tambun Selatan, in the academic year 2010/2011. The research method used was classroom action research. The survey results revealed that the observations and test cycle of I, II, and III. There wre incresed activity and students learning outcomes. The average value and the level of mastery learning students in cycle I at 61,14 with 40,91% completeness, increase in cycle II to 72,05 with 75,00% and increase in cycle III to 80,34 with 100% completeness. The conclusions of this research, there is an increase in mathematics learning outcomes on the subject ’Teorema Pythagoras’ with the implementation of ’improving learning’ and inquiry techniques of the students in grade VIII.2 SMPN 10 Tambun Selatan. Key words: Improving Learning, Inquiry, Teorema Pythagoras